Anti-aging potential of extracts from Sclerocarya birrea (A. Rich.) Hochst and its chemical profiling by UPLC-Q-TOF-MS - Tinotenda Shoko; Vinesh J. Maharaj; Dashnie Naidoo; Malefa Tselanyane; Rudzani Nthambeleni; Eric Khorombi; Zeno Apostolides (BMC, 2018)
Abstract Background Degradation of components of the extracellular matrix such as elastin and collagen by elastase and collagenase accelerates skin aging. Phytochemicals that inhibit the activity of these enzymes can be developed as anti-aging ingredients. In this study, an investigation of the anti-aging properties of Sclerocarya birrea (A. Rich.) Hochst (Marula) extracts was conducted in vitro with the aim of developing chemically characterized anti-aging ingredients. Methods Marula stems, leaves and fruits were extracted using methanol:dichloromethane (DCM) (1:1). The stems were later extracted using acetone, ethanol, methanol:DCM (1:1) and sequentially using hexane, DCM, ethyl acetate and methanol. The stem ethanol extract was defatted and concentrated. Elastase and collagenase inhibition activities of these extracts and Marula oil were determined using spectrophotometric methods. The chemical profile of the ethanolic stem extract was developed using Ultra-performance-liquid chromatography quadrupole-time-of-flight mass spectrometry (UPLC-Q-TOF-MS) with MassLynx software. Pure standards were used to confirm the identity of major compounds and were screened for anti-elastase and anti-collagenase activity. Results Marula stems extracts were the most active as they exhibited anti-elastase activity comparable to that of elafin (> 88%) and anti-collagenase activity as potent as EDTA (> 76%). The leaf extract had moderate anti-elastase activity (54%) but was inactive agains collagenase. Marula fruits and oil exhibited limited activity in both assays. The ethanolic extract of Marula stems was the most suitable based on its acceptability to the cosmetic industry and its anti-collagenase activity (99%). Defatting and concentration improved its antiaging activity and lowered the colour intensity. Six compounds have been tentatively identified in the chemical profile of the ethanolic extract of Marula stems of which four; quinic acid, catechin, epigallocatechin gallate and epicatechin gallate have been confirmed using pure standards. Epigallocatechin gallate and epicatechin gallate were as potent (p < 0.05) as EDTA at 5 μg/ml in the anti-collagenase assay. Conclusions The ethanolic extract of Marula stems can be developed into an anti-aging ingredient as it exhibited very good in vitro anti-aging activity and its chemical profile has been developed. Epicatechin gallate and epigallocatechin gallate contribute to the anti-aging activity of Marula stem ethanol extract.